Programa estrategias lúdicas para desarrollar el lenguaje oral en niños de 5 años nivel inicial de la institución educativa 601491 Madre Teresa de Calcuta San Juan 2023 - Rios Lopez, Luz Priscila (2025)
The research entitled Program of playful strategies to develop oral language in 5-year-old children at the initial level of the Educational Institution 601491 Madre Teresa De Calcutta. Saint John. 2023. The study employed an applied research approach with a quasi-experimental design. The sample was made up of 25 children from the control group and 25 children from the experimental group. A program was developed and implemented using methodological strategies to address the language development needs of 5-year-old children, as indicated by evidence. The results indicate that the implementation of the playful strategies program in oral language generated a significant increase in the post-test scores. Specifically, the experimental group showed a 0% increase in the low range, a 16% increase in the medium range, and an 84% increase in the high range, compared to the control group where the program was not implemented. Consequently, the program had a beneficial impact on children's learning.